Highly sensitive sequential injection determination of of p-aminophenol in paracetamol formulations with 18- molybdodiphosphate heteropoly anion based on elimination of Schlieren effect - Vishnikin, Andriy B.; Вишнікін, Андрій Борисович; Al-Shwaiyat, Mohammed K.E.A.; Аль-Швайят, Мохаммед К.Е.А.; Petrushina, Galina A.; Петрушина, Галина Олександрівна; Tsiganok, Ludmila P.; Циганок, Людмила Петрівна; Andruch, Vasil; Андруч, Василь; Bazel, Yaroslav R.; Базель, Ярослав Р.; et al. (Elsevier, 2012)
A highly sensitive, precise and automated method using sequential injection analysis to assay quantitatively low levels of the p-aminophenol (PAP) in paracetamol formulations has been developed. A solution containing PAP and paracetamol is injected into an acetate buffer carrier stream and merged on-line with 18-molybdodiphosphate heteropoly complex reagent to form a specific blue derivative that is subsequently detected spectrophotometrically at 820 nm. The procedure has been optimized mainly with respect to measurement sensitivity. It is based on the leveling off of the refraction indices of the liquids mixed in the flow system by the careful matching of the refractive index of the reagent solution with that of the carrier and sample solutions. Amount as low as 0.5 μmol L−1 of PAP, which corresponds to the 0.001% of PAP in paracetamol tablets, can be reliably determined using the proposed method, which is clearly below the specification limits recommended for PAP determination in paracetamol drug and tablet formulations (50 ppm or 0.005% (w/w)). The developed method was successfully applied to the analysis of paracetamol formulations spiked with PAP and determination of PAP content in Rapidol tablets past their expiration date both by proposed SIA and reference HPLC methods. Розроблено високочутливий, точний та автоматизований метод із застосуванням аналізу послідовного введення для кількісного аналізу низьких рівнів п-амінофенолу (PAP) у композиціях парацетамолу. Розчин, що містить PAP і парацетамол, вводять в потік ацетатного буфера-носія і зливають в режимі онлайн з 18-молібдодифосфатним гетерополікомплексним реагентом для утворення специфічної синьої похідної, яка згодом виявляється спектрофотометрично при 820 нм. Процедуру було оптимізовано в основному щодо чутливості вимірювання. Він заснований на вирівнюванні показників заломлення рідин, змішаних у проточній системі, шляхом ретельного узгодження показників заломлення розчину реагенту з показником заломлення носія та розчинів зразка. За допомогою запропонованого методу можна достовірно визначити кількість лише 0,5 мкмоль/л PAP, що відповідає 0,001% PAP у таблетках парацетамолу, що є явно нижчим за межі специфікації, рекомендовані для визначення PAP у препаратах парацетамолу та таблетках. (50 ppm або 0,005% (w/w)). Розроблений метод був успішно застосований для аналізу препаратів парацетамолу з додаванням ПАП та визначення вмісту ПАП у таблетках Рапідолу після закінчення терміну придатності як запропонованим методом SIA, так і еталонним методом ВЕРХ.
Високочутливе послідовне визначення п-амінофенолу в композиціях парацетамолу з 18-молібдодифосфат гетерополіаніоном на основі усунення ефекту Шлірена
Keywords: Determination of p-aminophenol with 18-molybdodiphosphate by SIA method; Визначення п-амінофенолу з 18-молібдодифосфатом методом SIA; A new strategy has been proposed to reduce the Schlieren effect; Запропоновано нову стратегію зменшення ефекту Шлірена; Careful matching of the reagent and buffer concentrations decreases Schlieren effect; Ретельний підбір концентрацій реагенту та буфера зменшує ефект Шлірена; Using new strategy allowed to improve sensitivity by one order of magnitude; Використання нової стратегії дозволило підвищити чутливість на один порядок; Amount as low as 0.001% of p-aminophenol can be determined in paracetamol tablets; У таблетках парацетамолу можна визначити лише 0,001% p-амінофенолу